ROLE OF GOVERNMENT AGENCIES IN THE PRESERVATION OF TANGIBLE HERITAGE; A CASE STUDY OFLAHORE IN PAKISTAN (Pakistan Journal of Science, 2022)
Cultural heritage of any country reflect the living styles of people and it show the identity of one nation. People inherit this style from the history and their ancestors. In order to preserve the cultural heritage in Pakistan, different departments are working at the national as well as provincial and local levels. These departments are trying to preserve the cultural heritage by keeping themselves involved in their defined domains. Unfortunately, till now, apart from presence of all the relevant departments the desired results could not be achieved. The reasons for this are many and the most important proved to be the lack of coordination among the line departments whether working at the central or local levels. The results thus are appearing in form of deterioration of country’s cultural heritage. This paper mainly explores the reasons of deterioration of cultural heritage.
Keywords: Tangible Heritage; Preservation Issues; Government Departments